2019
DOI: 10.18805/lr-3841
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Attributes as Influenced by Nutrient Management Practices in Pigeonpea and Clusterbean Intercropping System

Abstract: A filed experiment was conducted at College of Agriculture Farm, Gwalior on sandy clay loam soil during Kharif-2012 and 2013 to study the influence of nutrient management practices in pigeonpea and clusterbean intercropping system. On the basis of two year pooled data, results revealed that sole pigeonpea and clusterbean recorded significantly higher seed and stalk yield, harvest index, number of pods/plant, test weight, protein content, protein yield, dry matter/plant. Among the intercropping treatments T 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It could also be due to reduced interspecific and intraspecific competition between component crops in this intercropping system. In agreement with this research different authors [47,48], confirmed that intercropping significantly affected the number of primary branches. There was a significant difference in the number of primary branches by cropping systems.…”
Section: Number Of Primary Branchessupporting
confidence: 89%
“…It could also be due to reduced interspecific and intraspecific competition between component crops in this intercropping system. In agreement with this research different authors [47,48], confirmed that intercropping significantly affected the number of primary branches. There was a significant difference in the number of primary branches by cropping systems.…”
Section: Number Of Primary Branchessupporting
confidence: 89%
“…The gross return was significantly This is reflected in the enterprise's greater benefit-cost ratio, which were 2.01. Kushwah et al, 2017 andRajput andRawat (2019) both observed similar findings.…”
Section: Cost and Returns Structurementioning
confidence: 65%
“…Pigeonpea when grown during the rainy season as a sole crop, with less fertile soil, results in poor yield. Modification of few agro-techniques can play a significant role to enhance the productivity and profitability through efficient utilization of land, moisture, and solar energy (Kumar et al, 2016;Rajput and Bhadouriya, 2019).…”
mentioning
confidence: 99%